Determination of Lead and Cadmium Content of Dill (Anethum graveolens) and Onion (Allium Cepa L.) Cultivated in Khozestan/Iran: Pb and Cd in Khozestan dill and onion - Zahra Ramezani; Nasrin Aghel; Roohollah Shiralipour; Reza Zadeh Dabbagh (Iranian Journal of Pharmaceutical Sciences, 2011)
In this study, 60 composite samples of dill and onion from two different cultivated areas in Khozestan province, Iran, were collected and analyzed for the presence and determination of lead and cadmium by flame atomic absorption spectrometry. Samples were burned according to AOAC at 450 °C, and the residue was dissolved in nitric acid. Lead and Cadmium contents were determined using calibration curves at wavelength 217 and 283.8 nm, for Cd and Pb, respectively. In order to evaluate reliability of the results obtained by external calibration curve, standard addition data for a number of randomly selected samples were compared with those of calibration. The results were in good agreements. Two Samples of each vegetable were also spiked with a certain amount of Pb and Cd. The recoveries of standards were in the range of 90-110%. Reproducibility was also good. Mean Cd and Pb concentrations were 0.208, and 1.972 mg.kg-1 dill, respectively. In the case of onion, no lead was detected, but its cadmium content was 0.0475 mg.kg-1. Pb and Cd content of dill were higher than permitted limits reported in Codex.